2021
DOI: 10.3389/fimmu.2021.748423
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ligand Specificity and Functional Plasticity in Type I Interferon Signaling

Abstract: The Type I Interferon family of cytokines all act through the same cell surface receptor and induce phosphorylation of the same subset of response regulators of the STAT family. Despite their shared receptor, different Type I Interferons have different functions during immune response to infection. In particular, they differ in the potency of their induced anti-viral and anti-proliferative responses in target cells. It remains not fully understood how these functional differences can arise in a ligand-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 88 publications
(211 reference statements)
2
19
0
Order By: Relevance
“…However, experiments have shown that the interferon pathway does not only qualitatively discriminate between the ligands, but also quantitatively responds differently to specific ligand doses [ 40 ]. By combining diverse data sets from different experimental systems using a minimal computational model, it was recently shown that while these differences in ligand binding strengths are theoretically sufficient for ligand discrimination, experiments failed to show a region of absolute discrimination between IFNα and IFNβ [ 41 ]. Rather, the mathematical model based on previous experimental data [ 42 ] showed that the negative feedback loop via USP18 contributes to ligand discrimination.…”
Section: Cytokine Waves Augmenting or Diminishing Pathway Activation ...mentioning
confidence: 99%
“…However, experiments have shown that the interferon pathway does not only qualitatively discriminate between the ligands, but also quantitatively responds differently to specific ligand doses [ 40 ]. By combining diverse data sets from different experimental systems using a minimal computational model, it was recently shown that while these differences in ligand binding strengths are theoretically sufficient for ligand discrimination, experiments failed to show a region of absolute discrimination between IFNα and IFNβ [ 41 ]. Rather, the mathematical model based on previous experimental data [ 42 ] showed that the negative feedback loop via USP18 contributes to ligand discrimination.…”
Section: Cytokine Waves Augmenting or Diminishing Pathway Activation ...mentioning
confidence: 99%
“…Ligand-receptor signaling kinetics is the first step in signaling cascades that strongly influences the communication fidelity and the reliability of the resulting cellular responses [1][2][3]. Many receptor signaling systems require high signaling specificity -the degree to which a cell can respond differently to different ligands based on the differences in their binding affinities to the receptor [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Sustained IFN-I expression bears deleterious effects on host immunity [ 6 , 7 , 8 ]. The mechanisms of the virus escaping intracellular defences are not completely understood [ 9 , 10 , 11 ] because they include multiple layers of control of IFN-I signalling [ 12 ] and diverse roles of interferon-stimulated gene (ISG) products [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the current work was to formulate and calibrate a stochastic model of HIV-1 replication that includes antiviral responses of an infected cell and to apply it to examine the dependence of virus production and IFN-I secretion on antiviral defence reactions. This requires the application of computational modelling tools, which corresponds to the mainstream trends in immunology and virology [ 12 , 18 ]. Specifically, we aimed to: Develop an analytical tool for data assimilation and analysis of HIV-1 replication and the IFN-I response; Identify the control points underlying the viral ability to evade IFN-I-mediated defences as they represent potential targets for antiviral and immune therapies; Predict the effective reproduction number of single-cell infection resulting from the competition of multiple factors related to viral and IFN-I-dependent products.…”
Section: Introductionmentioning
confidence: 99%